Analisis Faktor-Faktor Kesulitan Menulis Huruf Abjad Bahasa Arab - Hanif Irfan (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2019)
The problem behind this research is that students’ difficulty in writing the letters of the Arabic alphabet and connecting letters to a word. The purpose of this research is to find out the factors that cause students difficulties in writing Arabic alphabet letters. This research method uses descriptive qualitative research design with a case study approach.The results of the research has shows that students were still very difficult in writing Arabic alphabet. The student’s category of difficulty is the difficulty in writing the letters of the Arabic alphabet either standing or straying, and the placement of the letters is still wrong. Then the letter writing which is considered difficult is the letters د, ذ, س, ش, ص, ض, ط, ظ, ف, ق, م, و, هـ ي . As for the causes of students’ difficulty in writing the letter of the Arabic alphabet, it comes from both internal and external factors. Internal factors include students do not memorize the letters of the Arabic alphabet, lack of talent, interest and motivation. External factors include means and less supportive learning infrastructure, and the learning methods and media used by the teacher are less varied.